(untitled) (Journal of Current and Advance Medical Research, 2015)
Background: The pattern of dyslipidemia varies among the patients of type 2 of diabetes mellitus. Objective: The purpose of the present study was to observe gender difference of lipid abnormalities in type-2 Diabetes Mellitus patients. Methodology: This cross sectional comparative study was conducted in the OPD of Department of medicine at BIRDEM, Dhaka from January, 2014 to July, 2014 for a period of six months. Convenient purposive sampling method was used and data assessed in a prospective manner. Blood sugar (FBS, ABF), lipid profile (TG, TC, LDLC, and HDLC) were measured. Statistical analyses were performed with the SPSS software program. Results: A total number of 400 type 2 DM patients (200 males and 200 females) attending to BIRDEM OPD were recruited in this study. Blood sugar was higher than normal in both male and female (FBS=8.79±.20, 8.64±0.22 respectively and ABF=12.15±0.27, 11.8±0.29 mmol/l respectively). TG level was also higher in two groups of study subjects with male level is slightly more than female (194.99±6.72 and 185.21±15.51 respectively) with no significant difference between the groups (P>.05). Total cholesterol and LDL-C level was within normal physiological level in both groups, where as these levels were higher in female in comparison to male (TC=184.44±3.33 &166.16±3.04 respectively, LDLC=109.68±2.59 & 88.66±2.59 respectively), showing significant difference between the groups (P=.000). HDL-C was below normal in both male (38.28± 48) and female (39.02±2.59); however HDL-C was slightly higher in female than male and the difference was insignificant (p=.330). Conclusion: In conclusion dyslipidemia were observed in a greater proportion of female diabetic patients than male diabetic patients. Journal of Current and Advance Medical Research, 2015;2(2):34-38